Zastosowanie komputerowego rachunku symbolicznego do zagadnień zginania belek - Hałat, Włodzimierz (My University, 2007)
CAS Calculations methods (Computer Algebra System) take a special position in supporting software packages for technical scientific research works. They can be used for a wide range of advanced applications in various engineering solutions including constructions and geotechnics. With the symbolic calculations method it has been presented the role of support onto: reaction forces, bending moments, transversal forces, bending angles and profile lines in the beams under bending process. The results in the form of symbolic mathematical formulas are illustrated with diagrams that have been plotted obviously based on number values but not symbols.

Systemy obliczeniowe zwane CAS (ang. Computer Algebra System) zajmują szczególne miejsce wśród pakietów programów wspomagających prace naukowo-techniczne. Mają one szerokie możliwości rozwiązywania zaawansowanych zadań z różnych dziedzin inżynierskich, w tym także problemów związanych z geotechniką i budownictwem. Za pomocą rachunku symbolicznego przedstawiono wpływ podparcia na wartości: sił reakcji, momentów zginających, sił tnących, kątów ugięcia i linii ugięcia w zginanych belkach. Otrzymane rozwiązania, w postaci symbolicznych wzorów matematycznych, zostały zobrazowane wykresami. Wykresy z konieczności narysowane zostały na wartościach liczbowych, a nie symbolicznych.
Use of computer algebra system for beams' bending problems
Górnictwo i Geoinżynieria
Bibliogr. s. 182.
Keywords: CAS packages; pakiety CAS; symbolic calculations; rachunek symboliczny; beam bending; zginane belki; reactions; reakcje; bending moments; momenty zginające; transversal forces; siły tnące; bending angles; kąty ugięcia; bending profile line; linia ugięcia